The Effectiveness of Peer Tutoring on Students' Understanding of Mathematical Concepts - Yoviyanti, Rifkah; Wahyudi; Suhendar, Uki; Zuraidah, Zuraidah (Jurnal Pedagogi dan Pembelajaran, 2023)
The low understanding of students in mathematics is due to the need for more use of learning methods that attract students to participate in learning well. The research aims to analyze the effectiveness of using peer tutoring learning methods on students' ability to understand mathematical concepts. This research is a quasi-experimental research with a Pretest-Posttest research design. The research population includes students from the Guidance Studio. Data collection methods use observation and tests. The research instrument includes a test of understanding mathematical concepts. Data analysis in this study used an independent sample T-test because the data is normal. The analysis results show that the increase in the ability to understand mathematical concepts for students who apply the peer tutoring method is better than those who use conventional learning. The peer tutoring method is more effectively applied in mathematics learning towards students' understanding of mathematical concepts. Therefore, peer tutoring is more effective in improving students' understanding of mathematical concepts in the classroom learning process. This research implies that applying the peer tutor learning method is very useful, especially for teachers, which can be used as an alternative learning method in schools to improve students' understanding of mathematical concepts.